(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Acta Conventus Neo-Latini Sanctandreani, Proceedings of the Fifth International Congress of Neo-Latin Studies, Binghamton-New York, Ed. I. D. McFarlane, 1986, 645 pp.